A Meta-Analysis: The Development of Research on Religiosity To Academic Resilience At Islamic Educational Institutions 2015-2024 - Syatria Adymas Pranajaya; T Zulfikar; Sehat Ihsan Shadiqin; Ani Cahyadi; Nur Kholik Afandi (Sustainable, 2024)
This study aims to map the development of research on religiosity and academic resilience in Islamic educational institutions 2015-2024. Meta-analysis was conducted on 23 studies, which then narrowed down to 6 studies because they were not included in the inclusion statement, such as research outside of Islamic educational institutions. Meta-analysis itself is a review of several research results on similar issues. Searches from various sources to find the study in question, namely from articles (research results) in journals and academic reports from a survey through Google Scholar, Scispace, Publish and Perish which are open access. This meta-analysis aims to find out the distribution of research according to the title and inclusion statement, as well as analyze the research objectives, research methods, research population/sample, and data collection methods/techniques that are most dominantly used in the title. This analysis showed that the six studies that fit the inclusion statement were in Indonesia. Another finding based on the dominant research objective is to know the relationship by 50%, then the method of interest is quantitative with a rate of 83.33%. Meanwhile, the population/sample and subjects in these studies were 100% students. Furthermore, the dominant data collection method/technique in the 6 studies is a questionnaire, which is 66.66%. Finally, the results of these studies all state that religiosity has a relationship with and influence on academic resilience in Islamic educational institutions. This proves that religiosity is essential in improving students' academic resilience.